2012
DOI: 10.1111/j.1600-0625.2012.01480.x
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐ageing potential of a new jasmonic acid derivative (LR2412): in vitro evaluation using reconstructed epidermis episkin™

Abstract: Jasmonic acid is involved in plant wound repair and tissue regeneration, but no study has been reported in human skin. The effect of a jasmonic acid derivative, tetra-hydrojasmonic acid (LR2412, 1 and 10 lm) was investigated on an in vitro reconstructed skin model, Episkin TM . Using real time RTQPCR studies, results showed an increase in hyaluronan synthase 2 (HAS2) and hyaluronase synthase 3 (HAS3) expression. Furthermore, an increase in hyaluronic acid (HA) deposits in basal and suprabasal layers of the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The same requirement is true for botanical extracts, as efficacy data are often limited to just one or two studies, many of which were conducted in vitro and therefore may not relate to an in vivo environment. Despite these limitations, the available data suggest that some botanical extracts may act as topical interventions for photoageing [86][87][88].…”
Section: Are Otc Formulations and Their Constituent Ingredients Effecmentioning
confidence: 96%
See 2 more Smart Citations
“…The same requirement is true for botanical extracts, as efficacy data are often limited to just one or two studies, many of which were conducted in vitro and therefore may not relate to an in vivo environment. Despite these limitations, the available data suggest that some botanical extracts may act as topical interventions for photoageing [86][87][88].…”
Section: Are Otc Formulations and Their Constituent Ingredients Effecmentioning
confidence: 96%
“…However the in vivo efficacy and composition of many of these formulations have yet to be scientifically validated. Certain extracts are suggested to exert a preventative effect through antioxidant activity [82] whilst others have been implicated in dermal matrix repair through MMP inhibition or deposition of ECM components [83][84][85][86][87][88][89][90][91][92][93] (Table 2). For many of these botanical extracts, few studies have been published, little is known of their potential mechanisms of action and problems with batch to batch consistency plague attempts to define their molecular compositions.…”
Section: Botanical Extracts and Plant Derived Compoundsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the functional role of microalgal endogenous phytohormones remains elusive, molecular evidence from the oleaginous microalgae Nannochloropsis oceanica suggests that endogenous abscisic acid and cytokinin are functional, and that their physiological effects are similar to those in higher plants [49]. That means the microalgal phytohormones could play a role in counteracting signs of skin ageing [50], a promising future in skin care cosmetics.…”
Section: Uses Of Microalgae and Cyanobacteria For Cosmetic Applicationsmentioning
confidence: 99%
“…Therefore, itwas concluded that the JAs control tuber formation indirectly through crosstalk with GA signaling (Wasternack and Hause, 2013). Recently Michelet et al, 2012 found that one of the derivatives of the jasmonic acid, namely tetra-hydro jasmonic acid (LR2412) has shown anti-aging potential in case of human skin. LR2412 is known to increase the expression of hyaluronase synthase 2 (HAS2) and hyaluronase synthase 3 (HAS3) which consequently increase the synthesis of hyaluronic acid (HA) Plants are associated with diverse microbial communities that influence their health and nutrition.…”
Section: Introductionmentioning
confidence: 99%